DETECTING DIFFERENCES IN VEGETATION AMONG PAIRED SITES USING POLLEN RECORDS - Sugita Sh.; Parshall T.; Calcote R. (My University, 2006)
The ‘Qualitative Assessment of Difference’ method (QAD) is proposed to objectively detect differences in the relative abundance of vegetation between paired sites using pollen percentages. This method corrects for intertaxonomic differences in pollen productivity and neutralizes influences of background pollen on pollen representation of vegetation, using an inverse form of the Extended R-value model. We test the method using modern pollen-vegetation data from small hollows in northern Michigan (6 taxa; 45 sites) and from northwestern Wisconsin (7 taxa; 43 sites) in the USA. Compared with pollen percentages, the one-tailed Fisher Exact test shows that the QAD method significantly improves the accuracy of the results for all taxa. The rank order of sites based on QAD is significantly correlated to the rank order of sites based on a survey of vegetation composition surrounding the hollow for each taxon (Spearman’s rank-order correlation coefficients; p
Keywords: QUALITATIVE ASSESSMENT OF DIFFERENCE (QAD); POLLEN PERCENTAGES; PALYNOLOGY; ERV MODELS; BACKGROUND POLLEN; VEGETATION RECONSTRUCTION; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен